A Cross‐Cultural Study of Task Specificity in Creativity. (28th October 2015) - Storme, Martin; Lubart, Todd; Myszkowski, Nils; Cheung, Ping Chung; Tong, Toby; Lau, Sing
Abstract: This study provides new evidence concerning task specificity in creativity—examining through a cross‐cultural perspective the extent to which performance in graphic versus verbal creativity tasks (domain specificity) and in divergent versus convergent creativity tasks (process specificity) are correlated. The relations between different creativity tasks in monocultural and multicultural samples of Chinese and French children were compared. Electronic versions of the Wallach and Kogan Creativity Test (WKCT, Wallach & Kogan, 1965; Lau & Cheung, 2010) and the Evaluation of Potential Creativity (EPoC; Lubart, Besançon, & Barbot, 2011; Barbot, Besançon, & Lubart, 2011) were used. Both measures showed satisfactory psychometric properties and cross‐cultural structural validity. The results showed that culture has an impact on the structure of creative ability: It appeared that correlation patterns were different across Chinese and French groups and across monocultural and multicultural groups. Such results show that it is crucial to take task specificity into account when investigating the effect of culture on creativity. Indeed, our study implies that cultural differences that are found using one specific creativity task might not be automatically generalizable to all sorts of creativity tasks. Limitations are discussed and perspectives for future research on culture and task specificity in creativity are proposed.